A pathogenesis‐related protein GmPR08‐Bet VI promotes a molecular interaction between the GmSHMT08 and GmSNAP18 in resistance to Heterodera glycines. Issue 8 (5th February 2020) - Lakhssassi, Naoufal; Piya, Sarbottam; Bekal, Sadia; Liu, Shiming; Zhou, Zhou; Bergounioux, Catherine; Miao, Long; Meksem, Jonas; Lakhssassi, Aicha; Jones, Karen; Kassem, My Abdelmajid; Benhamed, Moussa; et al.
Summary: Soybean cyst nematode (SCN, Heterodera glycines) is the most devastating pest affecting soybean production worldwide. SCN resistance requires both the GmSHMT08 and the GmSNAP18 in 'Peking'‐type resistance . Here, we describe the molecular interaction between GmSHMT08 and GmSNAP18, which is potentiated by a pathogenesis‐related protein GmPR08‐Bet VI. Like GmSNAP18 and GmSHMT08, GmPR08‐Bet VI expression was induced in response to SCN and its overexpression decreased SCN cysts by 65% in infected transgenic soybean roots. Overexpression of GmPR08‐Bet VI did not have an effect on SCN resistance when the two cytokinin‐binding sites in GmPR08‐Bet VI were mutated, indicating a new role of GmPR08‐Bet VI in SCN resistance. GmPR08‐Bet VI was mapped to a QTL for resistance to SCN using different mapping populations. GmSHMT08, GmSNAP18 and GmPR08‐Bet VI localize to the cytosol and plasma membrane. GmSNAP18 expression and localization hyper‐accumulated at the plasma membrane and was specific to the root cells surrounding the nematode in SCN‐resistant soybeans. Genes encoding key components of the salicylic acid signalling pathway were induced under SCN infection. GmSNAP18 and GmPR08‐Bet VI were also induced under salicylic acid and cytokinin exogenous treatments, while GmSHMT08 was induced only when the resistant GmSNAP18 was present, pointing to the presence of a molecular crosstalk between SCN‐resistant genes and defence genes. Expression analysis of GmSHMT08 and GmSNAP18 identified the need of a minimum expression requirement to trigger the SCN resistance reaction. These results provide insight into a new response mechanism towards plant nematode resistance involving haplotype compatibility, gene dosage and hormone signalling.